2015
DOI: 10.1039/c5sm00926j
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming inactivation of the lung surfactant by serum proteins: a potential role for fluorocarbons?

Abstract: In many pulmonary conditions serum proteins interfere with the normal adsorption of components of the lung surfactant to the surface of the alveoli, resulting in lung surfactant inactivation, with potentially serious untoward consequences. Here, we review the strategies that have recently been designed in order to counteract the biophysical mechanisms of inactivation of the surfactant. One approach includes protein analogues or peptides that mimic the native proteins responsible for innate resistance to inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 137 publications
0
30
0
Order By: Relevance
“…Fluorocarbons can actually act as lung surfactant substitutes [249]. Effects on mammary gland development can differ from one strain of mice to another [235, 238,250].…”
Section: Animals Experience a Range Of Adverse Effects Usually At Himentioning
confidence: 99%
“…Fluorocarbons can actually act as lung surfactant substitutes [249]. Effects on mammary gland development can differ from one strain of mice to another [235, 238,250].…”
Section: Animals Experience a Range Of Adverse Effects Usually At Himentioning
confidence: 99%
“…Therefore, perfluorocarbons enriched with oxygen could help patients with acute respiratory distress syndrome (ARDS) continue breathing . They have also potential for lung surfactant replacement . To date, several studies have shown how fluorocarbons interact with interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] They have also potential for lung surfactant replacement. [10][11][12] To date, several studies have shown how fluorocarbons interact with interfaces. For example, fluorocarbon gases reduce the tension at the air/ water interface by 2-5 mN/m, suggesting their adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological assays are also commonly used to detect oxidative DNA damage through the use of an antibody or immunoglobulin . In situ hybridization provides information on specific changes in certain DNA sequences . Although several methodologies have been proposed to detect DSBs in DNA molecules, including the comet assay and single‐cell gel electrophoresis assay, it has been rather difficult to evaluate the number of DSBs per unit length of DNA in a quantitative manner, especially for long, genomic‐sized DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] For therapeutic purposes, various applications have been developedi ncluding the healing of wounds in skin, muscle and other tissues, hemostasis, transdermal drug delivery,t argeted drug delivery, in vivo oxygen delivery,a nd clot lysis. [7][8][9][10][11][12] With regard to these applications, it is important to evaluate the effect of ultrasound sonication on the living body and cells. [13][14][15] Ultrasound hasb otht hermal andn on-thermal effects.…”
Section: Introductionmentioning
confidence: 99%